2014
DOI: 10.1080/09500340.2014.982225
|View full text |Cite
|
Sign up to set email alerts
|

A dual-way directional surface-plasmon-polaritons launcher based on asymmetric slanted nanoslits

Abstract: 2014): A dual-way directional surface-plasmon-polaritons launcher based on asymmetric slanted nanoslits, Journal of Modern Optics,We theoretically design a device composed of two asymmetric slanted nanoslits to achieve the directionality of surface plasmon polaritons (SPPs). With proper inclination of the two slits, the desirable relative phase delay can be obtained. When the structure is illuminated by normal incident light, the SPPs can be controlled to deflect the specific direction due to light interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, a number of plasmonic structures have been proposed for SPP coupling. By employing asymmetric structures [8][9][10][11][12][13][14][15][16], incident angles [17], or positions [18], unidirectional SPP launching has been achieved. Interference effects between two or more SPP sources are commonly used for unidirectional SPP launching.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of plasmonic structures have been proposed for SPP coupling. By employing asymmetric structures [8][9][10][11][12][13][14][15][16], incident angles [17], or positions [18], unidirectional SPP launching has been achieved. Interference effects between two or more SPP sources are commonly used for unidirectional SPP launching.…”
Section: Introductionmentioning
confidence: 99%
“…When the size of a specific nanostructure is reached, SPPs can break through the limited conventional diffraction and control light on the nanoscale [ 3 , 4 ]. SPPs have three characteristics: low dimension and high intensity and subwavelength, which make them a good energy and information carrier, and their ability to combine subwavelengths can be used to make various optical devices [ 5 ], such as wavelength demultiplexers [ 6 , 7 ], plasmonic filters [ 8 , 9 ], logic gates [ 10 ], couplers [ 11 ], and sensors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, if SPP‐based devices are to be routinely included in the design of current integrated optical devices, an efficient and compact excitation scheme of the SPP in an integrated setting is required. There have been a number of advanced SPP excitation schemes proposed in the literature let alone the most commonly used SPP excitation schemes like the prism coupling in Otto or Kretschmann configurations and metallic grating coupling . Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of advanced SPP excitation schemes proposed in the literature let alone the most commonly used SPP excitation schemes like the prism coupling in Otto or Kretschmann configurations and metallic grating coupling. [9][10][11][12][13][14][15][16] Liu et al have demonstrated a high DOI: 10.1002/lpor.201700009 efficiency dual layer grating SPP excitation mechanism for a gold/air interface [16] ; whereas, Pors et al have demonstrated 1D and 2D gap resonators for directional excitation of SPP modes. [9] Such couplers are highly efficient, but are typically narrow in bandwidth and require out-of-plane bulky and angle sensitive setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation